2019
DOI: 10.3168/jds.2018-15939
|View full text |Cite
|
Sign up to set email alerts
|

Genomic selection improves the possibility of applying multiple breeding programs in different environments

Abstract: One joint breeding program (BP) for different dairy cattle environments can be advantageous for genetic gain depending on the genetic correlation between environments (r g ). The break-even correlation (r b ) refers to the specific r g where genetic gain with 1 joint BP is equal to the genetic gain of 2 environment-specific BP. One joint BP has the highest genetic gain if r g is higher than r b , whereas 2 environment-specific BP have higher genetic gain if r g is lower than r b . Genetic gain in this context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 11 publications
1
17
0
1
Order By: Relevance
“…To check the contribution of joint genomic evaluation, we simulated AG-WS in which the cooperation included only joint genomic evaluation, but selection was within environment. Results showed that even such a "single-layer" cooperation strategy was also beneficial for genetic gain and rate of inbreeding, as reported by Slagboom et al (2019). Subsequently when introducing the second level of cooperation, i.e.…”
Section: Improvements In Genetic Gain and Rate Of Inbreedingsupporting
confidence: 54%
“…To check the contribution of joint genomic evaluation, we simulated AG-WS in which the cooperation included only joint genomic evaluation, but selection was within environment. Results showed that even such a "single-layer" cooperation strategy was also beneficial for genetic gain and rate of inbreeding, as reported by Slagboom et al (2019). Subsequently when introducing the second level of cooperation, i.e.…”
Section: Improvements In Genetic Gain and Rate Of Inbreedingsupporting
confidence: 54%
“…However, under genomic selection schemes, this threshold of 0.80 between two traits for them to be appropriate to use one trait as an indicator for the other tends to be far higher under certain conditions (Slagboom et al, 2019). Yet, measurements using both methods on 10 3 to 10 4 related individuals are required to estimate genetic correlations with meaningful SEs (Visscher, 1998).…”
Section: Alternative Methods Of Recording Methane Emissionsmentioning
confidence: 99%
“…The correlation between the organic and the conventional BG was strong for both the Holstein and the Jersey breed and thus expected to be above the previously mentioned break-even correlation. This break-even correlation indicates the specific genetic correlation between BG for different environments above which it is better for genetic gain to have 1 common breeding program with 1 BG for the 2 environments instead of 2 breeding programs with an environment-specific BG for each environment (Mulder et al, 2006;Slagboom et al, 2019). The break-even correlation was estimated to be 0.61 by Mulder et al (2006) for a breeding program with progeny testing and 0.65 by Slagboom et al (2019) for a breeding program with genomic selection.…”
Section: Correlation Between Bgmentioning
confidence: 99%
“…Mulder (2007) suggested that the break-even correlation will be higher with genomic selection due to a possible higher intensity of selection. Slagboom et al (2019) showed by stochastic simulation that the break-even correlation is higher with genomic selection if the selection intensity is higher, but with the same selection intensity, the break-even correlation is the same. Differences in BG weights and G×E need to be combined to estimate the correlation between BG for organic and conventional dairy production.…”
Section: Introductionmentioning
confidence: 98%